SCIENTIFIC AND THEORETICAL BASIS FOR THE DEVELOPMENT OF STUDENTS' LINGUOMETHODOLOGICAL THINKING BASED ON THE PRINCIPLES OF AN INTEGRATIVE APPROACH (American Journal of Pedagogical and Educational Research, 2025)
The article examines the possibilities of developing students' linguistic and methodological thinking based on the principles of an integrative approach, principles of an integrative approach, linguistic and methodological thinking.